Regional variations and determinants of pesticide use among farmers in Southwestern Nigeria: implications for sustainable agriculture - Adeola, Abdullahi; van Gestel, Cornelis A. M.; Doherty, Victoria Funmilayo; Aneyo, Idowu Ayisat; Ajagbe, Folashade; Kasule, Faizo (Frontiers in Agronomy, 2025)
Pesticides are integral to the agricultural practices of Southwestern Nigeria, yet their varied usage patterns and the factors influencing their adoption remain poorly understood. Understanding pesticide usage is crucial for sustainable agricultural development. This study used a cross-sectional design and mixed-methods approach to examine pesticide usage, regional preferences, and pest control patterns in crop farming in Ogun, Ondo, and Oyo States, Nigeria. Data was collected from 472 farmers during the 2022 and 2023 farming seasons. Descriptive statistics, Pearson chi-square tests, and a generalized linear model were used to identify factors influencing farmers’ choices. Data were gathered through surveys and field observations from farmers in the three states. Pesticide usage varied across states, with Dichlorvos/DDVP (56.5%) and Lambda-cyhalothrin (49.8%) being the most common insecticides. Glyphosate (81.9%) and Paraquat (69.1%) dominated herbicide application, while Mancozeb emerged as the most widely used fungicide (38.6%). Imidacloprid and Thiram were the most used pesticide mixtures (44.5%), with significant variations observed across regions (χ² = 14.27, p < 0.001). Ondo State farmers preferred physical control methods (97.3%), Ogun State favored biological (67.3%) and botanical approaches (66.7%), while chemical control was predominant in Ondo (98.0%) and Oyo (99.4%). Demographic factors, including gender (F = 4.13, p = 0.04), education level (F = 3.59, p = 0.002), and farming locality (F = 1.56, p = 0.003), significantly impacted the adoption of specific pesticides and their mixtures. The study highlights the diverse crop protection strategies employed across Southwestern Nigeria and underscores the need for region-specific interventions. Tailored educational programs and resource allocation that consider local environmental conditions and demographic factors are essential for promoting sustainable agricultural practices and reducing chemical dependency. Addressing these regional and demographic disparities will enhance pest management effectiveness and support environmentally sustainable farming.